Siyude (senhorita): as “traduções” matses do contato histórico com missionárias do Summer Institute of Linguistics Sil - Dias, Ricardo Lopes [UNIFESP] (2015)
In the 2000s, a vision of an elderly woman radically changed the indigenous community of the Matsés people in the Brazilian Amazon. The central character of this vision was an evangelical missionary from the Summer Institute of Linguistics (SIL), or in the perspective of the Matsés, her mythical figure developed among the Brazilian communities. Ever since her initial contact in 1969, the relationship between the missionary and the people has developed unwanted interpretations, culminating in the mystification of his own figure and causing her to be feared as an architect of death and misfortune. The possibilities for anthropological analysis of this phenomenon are numerous and lead to different ramifications, when not conflicting. Presented here is a historical-anthropological analysis of the symbolic construction process of Siyude (Miss), the central character of this story, from considerations of authors working in this perspective as Marshall Sahlins, Eduardo Viveiros de Castro, Cristina Pompa and Paula Montero, among others. The empirical material consists of the memory as well as events and narratives, digitally archived by a also a missionary, now, a training anthropologist proposes a re-examination of the phenomenon seeking the Indian way of understanding otherness, his cosmological translation, in this case of the religious figure of an evangelical mission, articulating historical and linguistic factors of context.